2005
DOI: 10.1007/bf03194483
|View full text |Cite
|
Sign up to set email alerts
|

Size and overlap of home range inCalomys musculinus (Muridae: Sigmodontinae)

Abstract: 2005. Size and overlap of home range in Calomys musculinus (Muridae: Sigmodontinae). Acta Theriologica 50: 197-206.Home range size and overlap of Calomys musculinus (Thomas, 1913) was examined in relation to sex and breeding periods. The study was carried out in four 0.25 ha enclosures, in a natural pasture, between October 2002 and July 2003. The four enclosures functioned as independent populations and each was considered a replicate. The capture, mark and recapture method was used. Home range size and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 36 publications
(37 reference statements)
3
40
0
Order By: Relevance
“…This means, as suggested by Batzli and Henttonen (1993), that when home-range overlap is significantly lower than it would be expected by random distribution, individuals are avoiding one another. Steinmann et al (2005Steinmann et al ( , 2006a also found that during the breeding period, C. musculinus males' home ranges were twice as large as those of females and exhibited considerable overlap, with that of other males and of several breeding females. The greater home-range size and the intersexual overlap observed in males' home ranges might be a mechanism to increase the number of receptive females that they find to ensure optimal mating (Steinmann et al 2005(Steinmann et al , 2006a.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This means, as suggested by Batzli and Henttonen (1993), that when home-range overlap is significantly lower than it would be expected by random distribution, individuals are avoiding one another. Steinmann et al (2005Steinmann et al ( , 2006a also found that during the breeding period, C. musculinus males' home ranges were twice as large as those of females and exhibited considerable overlap, with that of other males and of several breeding females. The greater home-range size and the intersexual overlap observed in males' home ranges might be a mechanism to increase the number of receptive females that they find to ensure optimal mating (Steinmann et al 2005(Steinmann et al , 2006a.…”
Section: Introductionmentioning
confidence: 89%
“…Steinmann et al (2005Steinmann et al ( , 2006a also found that during the breeding period, C. musculinus males' home ranges were twice as large as those of females and exhibited considerable overlap, with that of other males and of several breeding females. The greater home-range size and the intersexual overlap observed in males' home ranges might be a mechanism to increase the number of receptive females that they find to ensure optimal mating (Steinmann et al 2005(Steinmann et al , 2006a. Sexual differences in home-range sizes and degree of overlap are considered a typical feature of rodent species with a promiscuous-polygynous mating system in which male spatial distribution is strongly influenced by search for mates and females are the territorial sex (Madison 1980;Gaulin and FitzGerald 1988;Heske and Ostfeld 1990).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, the proportion of dispersing individuals in this period is large (e.g. Steinmann et al 2005). The probability of a dispersing individual to be exposed to a larger variety of parasites is likely high.…”
Section: General Patterns Of Host and Flea Abundance And Diversitymentioning
confidence: 99%
“…The habitat use of C. musculinus has been studied by Simone et al (2012) in C ó rdoba Province and by Busch et al (2000) in Buenos Aires Province. The use of space by this rodent species has been widely studied by Steinmann et al (2005Steinmann et al ( , 2006aSteinmann et al ( ,b, 2009 . Only some aspects of microhabitat use for A. azarae in the breeding period have been dealt with by Bilenca and Kravetz (1998) in Buenos Aires Province.…”
Section: Ementioning
confidence: 99%